In vivo intervertebral disc mechanical deformation following a treadmill walking "stress test" is inversely related to T1rho relaxation time. Issue 1 (January 2023) - Coppock, J.A.; Zimmer, N.E.; Englander, Z.A.; Danyluk, S.T.; Kosinski, A.S.; Spritzer, C.E.; Goode, A.P.; DeFrate, L.E.
Summary: Objective: To assess the in vivo relationship between the mechanical response of intervertebral discs (IVDs) to dynamic activity and IVD biochemical composition assessed via T1rho relaxation imaging. Design: Eighteen asymptomatic participants with no history of low back pain (LBP), injury, or surgery underwent magnetic resonance (MR) imaging of their lumbar spine prior to and immediately following a treadmill walking "stress test." Anatomic (SPACE, FLASH) MR images were obtained pre- and post-exercise and utilized to measure IVD mechanical deformation. Quantitative (T1rho) imaging was performed pre-exercise to reflect IVD composition. Pre-exercise anatomic images were also utilized to assess IVD degenerative status based on the modified Pfirrmann scale. To quantify mechanical response, 3D surface models of the L1-L2–L5-S1 IVDs were created from manual segmentations of pre- and post-exercise anatomic images and utilized to assess changes in IVD height. IVD strain (%) was defined as change in IVD height normalized to pre-activity height. Linear mixed models were used to assess the relationships between IVD mechanical deformation (strain), composition (T1rho relaxation time), and degenerative status (Pfirrmann grade). Results: Increased compressive IVD strain was associated with lower T1rho relaxation times in the nucleus pulposus (NP) of the disc ( β T 1 r h o = 5.07, C I : [ 1.52, 7.77 ], R m a r g 2 = 0.52, p = 0.005 ) . Thus, an inverse relationship between IVD strain and NP T1rho relaxation time was observed. Conclusion: The in vivo mechanical response of the IVD to the "stress test" was sensitive to differences in NP composition. The results of this study suggest that quantification of in vivo IVD mechanical function and composition may provide insight into IVD health.